2019
DOI: 10.1111/1742-6723.13261
|View full text |Cite
|
Sign up to set email alerts
|

Affecting emergency department oxycodone discharge prescribing: An educational intervention

Abstract: Objective: To describe the impact of an educational intervention for ED prescribers on discharge oxycodone prescribing both for the number of oxycodone prescriptions per 1000 discharged patients, and the number of tablets per prescription. Secondary outcomes included the quality of general practitioner communication. Methods: An interrupted time series assessment was conducted in the ED of a tertiary referral hospital to establish the pre-intervention, periintervention and post-intervention prescribing profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 17 publications
2
49
1
Order By: Relevance
“…According to both the Norwegian General Practice criteria (NORGEP) and international (Beers and the screening tool of older people's prescriptions (STOPP)) criteria27–29 and treatment guidelines,22 23 opioid analgesics, benzodiazepines and z-hypnotics are all classified as inappropriate drugs for older patients and should not be used on a long-term basis. Our findings are consistent with three studies previously conducted in Norway,6 16 30 and suggest that today’s prescribing behaviour is suboptimal and that more indepth research and educational interventions are needed 31 32…”
Section: Discussionsupporting
confidence: 92%
“…According to both the Norwegian General Practice criteria (NORGEP) and international (Beers and the screening tool of older people's prescriptions (STOPP)) criteria27–29 and treatment guidelines,22 23 opioid analgesics, benzodiazepines and z-hypnotics are all classified as inappropriate drugs for older patients and should not be used on a long-term basis. Our findings are consistent with three studies previously conducted in Norway,6 16 30 and suggest that today’s prescribing behaviour is suboptimal and that more indepth research and educational interventions are needed 31 32…”
Section: Discussionsupporting
confidence: 92%
“…This is equivalent to a supply of up to 9845 prescriptions for as many as 165 899 tablets, into the local community each year. While smaller single-centre audits 10,11 have previously identified a common practice of oxycodone discharge prescribing in local EDs, our incidence is almost double that reported in Australia by Kline et al 11 (38 per 1000 discharges). It is reassuring however to find that this behaviour in our health service remains significantly lower than reported in the USA during the height of the opioid crisis.…”
Section: Discussioncontrasting
confidence: 58%
“…We suggest the provision of education for prescribers on the best practice use of opioids in acute pain, as well as the risks and public health consequences of these medications. Multiple educational interventions have been successful in reducing the incidence of oxycodone prescribing both within Australian and international EDs 15. Donaldson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have also focused on educating medical providers with proper prescribing practices . In a cohort of patients after Cesarean section and thoracic surgery, investigators found that majority reported taking half or less of the prescribed medication (83% Cesarean section vs. 71% thoracic surgery) .…”
Section: Measures To Address Opioid Use Storage and Disposal Issuesmentioning
confidence: 99%